Very high dielectric strength for dielectric elastomer actuators in liquid dielectric immersion - La, Thanh-Giang (2013)
This letter reported that a dielectric elastomer actuator (3M VHB), which is immersed in a liquid dielectric bath, is enhanced tremendously in dielectric strength up to 800 MV/m, as compared to 450 MV/m for the actuator operated in air. The bath consists of silicone oil (Dow Corning Fluid 200 50cSt), which is 6.5 times more thermally conductive than air, and it is found able to maintain the actuator at a stable temperature. As a result, the oil-immersed dielectric elastomer actuator is prevented from local thermal runaway, which causes loss of electrical insulation, and consequently avoids the damage by electromechanical instability